OCB pada Karyawan yang Sudah Menikah, Bagaimana Peran Work-Life Balance dan Perceived Organizational Support? - Sofiatul Azizah; Yanto Prasetyo; Hikmah Husniyah Farhanindya (JIWA: Jurnal Psikologi Indonesia, 2025)
AbstractThis study aims to determine whether there is a relationship between organizational citizenship behavior with work-life balance and perceived organizational support in married employees at Apartment. X. This analysis independent variable work-life balance and perceived organizational support with dependent variable organizational citizenship behavior. This research is a type of quantitative research using the correlational method. The sampling technique in this study used a random sampling method where the subjects were taken from the entire population of 86 respondents of Apartment employees. X employees who are married. The results of this study indicate that the first hypothesis is accepted, work-life balance and perceived organizational support have a positive relationship with organizational citizenship behavior. The second hypothesis is also accepted which shows that there is a positive relationship between work-life balance and organizational citizenship behavior. Meanwhile, the third hypothesis is not accepted, which means that there is no relationship between perceived organizational support and organizational citizenship behavior.Keywords: Work-Life Balance, Perceived Organizational Support, Employee, Organizational Citizenship BehaviorAbstrakPenelitian ini bertujuan untuk mengetahui apakah ada hubungan antara organizational citizenship behavior dengan work-life balance dan perceived organizational support pada karyawan yang sudah menikah di Apartemen. X. Analisis ini variabel independen work-life balance dan perceived organizational support dengan variabel dependen organizational citizenship behavior. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan metode korelasional. Teknik pengambilan sampel pada penelitian ini menggunakan metode random sampling yang dimana subjek diambil dari keseluruhan populasi sebanyak 86 responden karyawan Apartemen. X yang sudah menikah. Hasil penelitian ini menunjukkan bahwa hipotesis pertama diterima, work-life balance dan perceived organizational support memiliki hubungan positif dengan organizational citizenship behavior. Hipotesis kedua juga diterima yang menunjukkan bahwa terdapat hubungan positif antara work-life balance dengan organizational citizenship behavior. Sedangkan, untuk hipotesis ketiga tidak diterima yang berarti tidak ada hubungan antara perceived organizational support dengan organizational citizenship behavior.Kata kunci: Work-Life Balance, Perceived Organizational Support, Karyawan, Organizational Citizenship Behavior